PERSPEKTIF EKONOMI SYARIAH TERHADAP KEGIATAN JUAL BELI MELALUI MARKETPLACE ONLINE SHOPEE - Wahyuningsih, Wiwi; Safitri, Della Narti; Novita, Mia; Juliati, Nadia (Pusat Riset dan Publikasi, 2024)
The Shopee Marketplace is an online shopping platform that focuses more on user convenience, safe, fun, and practical by integrating social platforms. However, along with the development of the era that is increasingly modern, the business world tends to ignore ethics. In fact, the growing competition leads to contradictory practices, such as fraud, lies, and inappropriate goods. Just because to get as much profit as possible. Based on the background of the problem, the purpose of this study is to find out how the practice of buying and selling in the Shopee online marketplace and buying and selling through the Shopee online marketplace according to the review of Islamic business ethics. This article used a descriptive method through a qualitative approach with literature studies and descriptive analysis. The results of this study indicate that the Shopee online marketplace provides excellent service for users with the convenience of shopping anytime and anywhere. In addition, various promos and features offered on this platform are very diverse which provide great benefits for Shopee users. Some sellers on Shopee have implemented Islamic business ethics in online buying and selling transactions by paying attention to axioms such as unity, free will, responsibility, and balance. The original law of buying and selling is permissible, in accordance with the Al-Quran Surah Al Baqarah verse 275 which permits buying and selling and prohibits usury. Thus, buying and selling on Shopee is also permissible to do, except for the use of Shopee PayLater which contains elements of usury.